Legitimacy Of Presidential Election Results Due To Court Decision Conflict - Daming, Saharuddin; Husna, Mufidatul; Ibrani, Safira Adhwa (Universitas Ibn Khaldun Bogor, 2026)
This research aims to determine the legitimacy of the 2019 Presidential Election results in Indonesia in accordance with the Supreme Court’s decision Number 44 P/PHUM/2019 dated October 28, 2019, which annulled Article 3 Paragraph (7) of the General Elections Commission Regulation Number 5 of 2019 regarding the requirements for presidential and vice president candidacies. The Supreme Court's decision material contradicts law No.50/PUU-XII/2014 of the Constitutional Court, which is the basis for the publication of the General Elections Commission Regulation No. 5 of 2019. This contradicting law by the Constitutional and Supreme Courts is a challenge for Indonesia as a state because both have an equal footing to enforce justice due to conflicts associated with general elections. Unfortunately, the decisions of the two courts sometimes overlap in exercising their authority for Judicial Review. One of the problems that arise is whether the conflicting decisions of the Constitutional and Supreme Courts imply the legitimacy of the presidential election results. Another is determining the form of position and legal force in the interpretation of the Constitutional Court as the basis for the legitimacy of the Presidential Election results. However, the political reality and wisdom of Indonesian democratic constitutionalism show that the conflicting decisions of the Constitutional and Supreme Courts do not imply the legitimacy of these results. This is because the 1945 Constitution gives legal force to the Constitutional Court as an interpreter of the Erga Omnes principle. Therefore, to prevent similar conflicts in the future, the decisions of the two courts need to be synchronized to avoid legal dualism and uncertainty. In addition, the constitution and the election law need to be revised.